Interaktif Edukatif di Sekolah - Tutut Handayani (LPPM IAIN Sorong, 2015)
Theoretically, one of the dominant factors that influence the development of individual character are environmental factors which is a condition that allows the process of personal character development. Creating an conducive environment to the development of character Grikusumo Salaf Islamic School students is done by creating a tradition /habituation practical in everyday life in all their daily activities in relation to the quality of their religious or otherwise. Attempt the formation of character through this Salaf Islamic school in addition to the above character education can also be done simultaneously through the educational value of the following steps. First, apply a “modeling” or “exemplary” or “uswah hasanah”. Second, efforts to explain or clarify to students constantly about the value of good and evil has been done in the Girikusumo Salaf Islamic School. Third, implementing the SIS is based on character education. Character education is an important tool in the formation of student character. In practical guidance and counseling services in the schooling setting, character education is implemented through two ways, first directly through the services of guidance and counseling provided to students/ counselees, which are grouped into four components: (1) the component of basic service, (2) the component of responsive service, (3) the component of individual planning service, and (4) the components of the system support service. Loads of character education materials written in guidance and counseling services that include the areas of personal guidance, social guidance, learning guidance, career guidance, and character development. Second, indirectly, by example attitude and behavior of guidance and counseling teachers/counselors along with the cultivation of creative cultural, innovative, productive, collaborative, discipline, sense of belonging, and responsibility.